SISTEM INFORMASI GEOGRAFIS PENCARIAN RUTE OPTIMUM OBYEK WISATA KOTA YOGYAKARTA DENGAN ALGORITMA FLOYD-WARSHALL - Saputra, Ragil (MATEMATIKA, 2011)
The Information system based on spatial or Geographic Information System (GIS) is growing faster. GIS can be used to solve many problems, one of the solutions that GIS could address is for look optimum route base on start location and destination. By using GIS, user can get visual information. This research is implementing Floyd-Warshall algoritm for optimize route in Yogyakarta. Floyd-Warshall algoritm is part of dynamic programming which used for seek shorthes paths for every node/ verteks. The result of GIS application, it can beimplemented to determine the shortest path. The optimum shortes path information can help us to go to our destination faster.